2020
DOI: 10.1177/0017896920919777
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between coaches’ health promotion activities, sports experience and health among adults

Abstract: Objective: Health promotion in sports clubs is receiving increased attention, but its benefits have not been widely evaluated for two reasons: (1) the difficulty in measuring ecological approach outcomes and (2) the existing literature having focused more on coaches’ efficiency rather than on health promotion. This article analyses the relationship between coaches’ health promotion activities, sports experience and health among adult sports participants. Design: A cross-sectional study using self-reported meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Enjoyment in PA will be measured by using the Intrinsic Motivation Inventory (IMI) Questionnaire. This scale, not validated in French but used in different studies 23 among the sport population, determines the enjoyment in the practice of PA over a given period. Using four statements (eg, ‘I liked the activities I did’), responses are rated on a scale of 1–5, from 1, ‘strongly disagree’, to 5, ‘strongly agree’.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enjoyment in PA will be measured by using the Intrinsic Motivation Inventory (IMI) Questionnaire. This scale, not validated in French but used in different studies 23 among the sport population, determines the enjoyment in the practice of PA over a given period. Using four statements (eg, ‘I liked the activities I did’), responses are rated on a scale of 1–5, from 1, ‘strongly disagree’, to 5, ‘strongly agree’.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017 in France, 10.7 million patients (17% of the insured population) 1 were diagnosed with at least 1 of the 30 chronic diseases defined as 'diseases with an expensive and long-term treatment, which can be paid by the health insurance'. 23 Moreover, the prevalence of patients with chronic disease has increased by 4% between 2006 and 2011 and 5% between 2011 and 2017. 4 Beyond affecting individual health, chronic diseases also have high financial cost, estimated at €86 billion in 2015 in France.…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies have demonstrated that physical activity levels are closely associated with an individual's health status. Lack of physical activity often accompanies illnesses like cardiovascular disease, diabetes, and obesity [2]. It is also true that low levels of physical activity are strongly correlated to the incidence of diseases like cardiovascular disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of science and technology and economic takeoff, people are constantly improving their standard of living, but also face the increasing pressure of life; thus, the country is more concerned about the health of the people [1][2][3][4]. Exercise has been shown to reduce the risk of death by more than 25%, even when it is less than 5 MET-h per week, according to studies.…”
Section: Introductionmentioning
confidence: 99%